Os quatro passos iniciais da manutenção autônoma: implementação no setor de envase de uma usina de beneficiamento de leite - Mayer, Sthefani (2018)
Process improvement is something crucial to the great business competitiveness. Methodologies aimed at this goal are often used by companies that want to excel in this scenario. For this purpose, the present study aims to analyze the results that have been achieved through the implementation of the four initial steps of the autonomous maintenance. The study took place in the filling sector of a dairy processing plant in the state of Paraná. Positive results were generated in the filling sector and the beneficial repercussion on the activities of the operators were noticed. The indicators of mean time between failures and mean time to repairs also were improved.